"Cylindrical worlds" in biology: Does the aggregation strategy give a selective advantage?. (January 2019) - Filippov, A.E.; Guillermo-Ferreira, R.; Gorb, S.N.
Abstract: Tree trunks and other cylindrical objects, where aggregated insects live, represent a very specific world for predator-prey interactions, which must differ from the situation on a 2D plane. In the present paper, in order to gain a better understanding of the specificity of predator-prey interaction in a cylindrical space, we applied a theoretical approach. Here we introduce a numerical model that allows us to test the effect of different interaction properties between predator and aggregated prey on the plane (2D) and on a cylinder (3D), taking into consideration different abilities of predators to visually detect the prey in these two types of space. The main aim was to test these interactions in an environment, which more realistically reproduces the conditions where aggregated insects usually live. We showed that the aggregation in conjunction with a specific environment may bring additional advantages for the prey. When one prey subgroup aggregates on the other side of the tree trunk and becomes invisible behind the horizon of events for the predator, the subgroup will survive with an extremely high probability. After all, the predator moving along one side of the tree will finally loose the major group completely.